Stolen versus Wasted Waters of Pakistan - Prof. Dr. Umbreen Javaid; Hassan Iqbal (Journal of Political Studies, 2019)
Availability of per capita water is decreasing in Pakistan very fast. No serious effort has been done after the commissioning of Mangla and Tarbela dams long ago. The efficacy of these dams is also falling fast due to sedimentation. The construction of Kalabagh dam has been made politically controversial and Sindh, KPK and Baluchistan provinces are not even ready to consider the proposal. Successive Governments are dragging their feet on Diamer Bhasha dam due to its cost, long time required for completion and other logistic challenges. India, as upper riparian, is continuing with its designs to impede water flow towards Pakistan by building hydroelectric projects, and at some places even diverting water against the Indus Water Treaty 1960. Pakistan has already entered water stressed zone and experts are since long warning about this fact. It is said that the scarcity of water could prove to be a bigger threat than even the terrorism which Pakistan faced for almost 20 years. If it is politically Kalabagh dam is not feasible Pakistan should find alternatives, as there is no short cut solution to this problem. It has already been delayed for long and further delay shall cause clausal damages to economy, agriculture, industry, environment, ecology and above all national integration, as shortage of water is turning into inter provincial dispute.